The Qur’anic Readings and the Expressions of Acceptance and Rejection - Fadil, Ashwaq (International Conference on Islamic Studies, 2024)
This study aims to clarify the stage in which Qur’anic readings were recorded within the writings and works of other sciences before they developed into an independent, fully established discipline with its own foundational principles and specialized books. Highlighting this stage is essential because it represents the period when the science of Qur’anic readings overlapped with other scholarly fields, reflecting its gradual maturation and historical development. The research seeks to achieve its goal by answering key questions such as: In which scholarly writings were Qur’anic readings included? and Which books were exclusively devoted to this discipline?The researcher employed both the inductive and descriptive methods to present and analyze these works. While previous studies have examined the detailed overlap between the science of Qur’anic readings and other scientific compilations, this study offers a concise overview of that interrelation, avoiding unnecessary elaboration.The study concludes with findings, the most significant of which emphasize that critical evaluation in this field is based on firm foundations—namely, the Qur’anic text and reason—followed by a list of sources.